Alzheimer's disease genetic risk score and neuroimaging in the FINGER lifestyle trial - Saadmaan, Gazi (2024)
INTRODUCTION:We assessed a genetic risk score for Alzheimer’s disease (AD-GRS) and apolipoprotein E (APOE4) in an exploratory neuroimaging substudy of the FINGER trial.METHODS: 1260 at-risk older individuals without dementia were randomized to multidomain lifestyle intervention or health advice. N = 126 participants underwent magnetic resonance imaging (MRI), and N = 47 positron emission tomography (PET) scans (Pittsburgh Compund B [PiB], Fluorodeoxyglucose) at baseline; N = 107 and N = 38 had repeated 2-year scans.RESULTS: The APOE4 allele, but not AD-GRS, was associated with baseline lower hippocampus volume (β = −0.27, p = 0.001), greater amyloid deposition (β = 0.48, p = 0.001), 2-year decline in hippocampus (β=−0.27, p = 0.01), total gray matter volume (β = −0.25, p = 0.01), and cortical thickness (β = −0.28, p = 0.003). In analyses stratified by AD-GRS (below vs above median), the PiB composite score increased less in intervention versus control in the higher AD-GRS group (β=−0.60, p = 0.03). DISCUSSION: AD-GRS and APOE4 may have different impacts on potential intervention effects on amyloid, that is, less accumulation in the higher-risk group (AD-GRS) versus lower-risk group (APOE).